Stress corrosion crack initiation testing with tapered specimens in high-temperature water – results of a collaborative research project. (17th February 2021) - Bosch, Rik-Wouter; Ritter, Stefan; Herbst, Matthias; Kilian, Renate; Burke, M. Grace; Duff, Jonathan; Scenini, Fabio; Gu, Yuchen; Dinu, Alice; Ehrnstén, Ulla; Toivonen, Aki; Novotny, Radek; et al.
ABSTRACT: The applicability of an accelerated test technique using tapered tensile specimens for investigating the stress corrosion crack (SCC) initiation behaviour of structural materials in high-temperature water was assessed in the framework of a European collaborative research project (MICRIN – MItigation of CRack INitiation). The main advantage of using a tapered geometry is, that in a single test a stress gradient is obtained through the gauge length, and therefore a stress threshold for SCC initiation can be determined in a reasonable timeframe. This method was used to investigate two different materials that were known to be susceptible to SCC in light water reactor environment: a high-Si stainless steel and a Ni-base weld metal (Alloy 182). The results of the international test programme confirmed that the tapered specimen test methodology could be used to identify a SCC initiation stress threshold, albeit that significant scatter was present in the data.